(2x² + 7x - 8)(2x² + 7x - 3) - 6 =0
Сделаем замену :
2x² + 7x - 8 = m ⇒ 2x² +7x - 3 = m + 5
m * (m + 5) - 6 = 0
m² + 5m - 6 = 0
По теореме Виета :
m₁ = - 6 m₂ = 1
1) 2x² + 7x - 8 = - 6
2x² + 7x - 2 = 0
D = 7² - 4 * 2 * (- 2) = 49 + 16 = 65
2) 2x² + 7x - 8 = 1
2x² +7x - 9 = 0
D = 7² - 4 * 2 * (-9) = 49 + 72 = 121 = 11²
Объяснение:
Введём замену:
Перепишем исходное уравнение с учётом замены:
Решим уравнение при теоремы Виета:
Вернёмся к замене:
(2x² + 7x - 8)(2x² + 7x - 3) - 6 =0
Сделаем замену :
2x² + 7x - 8 = m ⇒ 2x² +7x - 3 = m + 5
m * (m + 5) - 6 = 0
m² + 5m - 6 = 0
По теореме Виета :
m₁ = - 6 m₂ = 1
1) 2x² + 7x - 8 = - 6
2x² + 7x - 2 = 0
D = 7² - 4 * 2 * (- 2) = 49 + 16 = 65
2) 2x² + 7x - 8 = 1
2x² +7x - 9 = 0
D = 7² - 4 * 2 * (-9) = 49 + 72 = 121 = 11²
Объяснение:
Введём замену:
Перепишем исходное уравнение с учётом замены:
Решим уравнение при теоремы Виета:
Вернёмся к замене: